2011
DOI: 10.1074/jbc.m110.168468
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of Clathrin-mediated Endocytosis in the Infectious Entry of Human Enterovirus 71

Abstract: Little is currently known about the infectious entry process of human enterovirus 71 (HEV71) into host cells, which may represent potential anti-viral targeting sites. In this study a targeted small-interfering RNA (siRNA) screening platform assay was established and validated to identify and profile key cellular genes involved in processes of endocytosis, cytoskeletal dynamics, and endosomal trafficking essential for HEV71 infection. Screen evaluation was conducted via the expression of well characterized dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
118
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 70 publications
9
118
1
1
Order By: Relevance
“…To further understand the process of EV71 internalization, we performed double staining of EV71 (in the absence of neutralizing MAbs) with the early and late endosome markers EEA1 and LAMP1, respectively. Colocalization of EV71 with EEA1 was observed as early as 5 min postinfection, increased afterwards, and was sustained until 60 min postinfection (the last time point tested), whereas colocalization of EV71 with LAMP1 was clearly seen from 30 to 60 min postinfection (data not shown), indicating that internalization and subsequent transport of EV71 virions to the early and late endosomes occur mainly within 15 to 30 min after infection, in agreement with the similar findings reported previously (50). By comparing the localization pattern and timing of EV71 in the presence of D5 to those in the absence of the antibody, it was concluded that the internalization of EV71 is prohibited by the D5 antibody treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To further understand the process of EV71 internalization, we performed double staining of EV71 (in the absence of neutralizing MAbs) with the early and late endosome markers EEA1 and LAMP1, respectively. Colocalization of EV71 with EEA1 was observed as early as 5 min postinfection, increased afterwards, and was sustained until 60 min postinfection (the last time point tested), whereas colocalization of EV71 with LAMP1 was clearly seen from 30 to 60 min postinfection (data not shown), indicating that internalization and subsequent transport of EV71 virions to the early and late endosomes occur mainly within 15 to 30 min after infection, in agreement with the similar findings reported previously (50). By comparing the localization pattern and timing of EV71 in the presence of D5 to those in the absence of the antibody, it was concluded that the internalization of EV71 is prohibited by the D5 antibody treatment.…”
Section: Discussionsupporting
confidence: 81%
“…For a given sample, the neutralization efficiency was calculated by normalization of its OD 490 value to that of the sample treated with virus only as follows: percent neutralization ϭ [(OD 490 of the given sample Ϫ OD 490 of the sample treated with virus only)/(OD 490 of the mock-treated sample Ϫ OD 490 of the sample treated with virus only)] ϫ 100. The 50% inhibitory concentration (IC 50 ) was defined as the MAb concentration that reduced cell death by 50%.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…The second receptor, reported by Yamayoshi et al (9), was human SCARB2, which is expressed on most types of cells (7). EV-71 binds to the SCARB2 receptor and is then internalized through clathrin-mediated endocytosis (47,48). However, blocking of these receptors did not abolish EV-71 infection, and this finding led to the discovery of the third receptor, annexin II.…”
Section: Discussionmentioning
confidence: 99%
“…The EF loop region of VP1, which lines the wall of the canyon on the viral surface, was found to be important for binding to SCARB2 (24). EV71 infection via the SCARB2-dependent pathway was inhibited by a small interfering RNA (siRNA) treatment against the molecules that are involved in the clathrin-dependent endocytic pathway and by inhibitors of endosomal acidification (25,26). In addition to EV71, coxsackievirus A7 (CVA7), CVA14, and CVA16 have utilized SCARB2 as a receptor for infection (17,22).…”
mentioning
confidence: 99%